Evolución de la deficiencia de oxígeno en la perovskita SrFeO2.5 mediante un proceso de reacción en estado sólido termodinámicamente controlado - Reyes Gordillo, Luis Emmanuel (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
The deficiency of oxygen is of great scientific interest due to the behavior of this material when is exposed in thermodynamically controlled and uncontrolled working environments. In addition, being used as precursor phase of more complex ceramic materials were brought under to a highly reducing atmosphere. However, when it was brought into contact under environmental conditions it presents a gradual decomposition, product of the chemical potential of the anionic phase that promotes the orderly oxygen deficiency, resulting in a mixture SrFeO2.5 + SrFeO2 with a high percentage of the theoretically unstable SrFeO2 phase. In this work precursor powders of SrCO3 (Aldrich, 99.9%) and Fe2O3 (Alfa Aesar, 99.9%) were dehumidified in a dry bed oven for 20 h at 100 ° C. Then, they were mixed in a 2:1 ratio in an agate mortar for 1h for later loading on a thermogravimetric balance where the synthesis of the SrFeO2.5 phase was carried out. Once the phase was obtained it was characterized by XRD and a successful and reproducible route for the synthesis of the SrFeO2.5 phase was verified. For the analysis of ordered oxygen deficiency samples of the SrFeO2.5 phase were brought under to inert, reducing and oxidizing atmospheres within a thermobalance, and to the environment exposed to the elements. Using the results of the thermogravimetric analysis (TGA) it was possible to relate the weight loss of each sample analyzed with the oxygen loss calculated by means of a product balance of the ordered oxygen deficiency in each evaluated condition. It was shown that the SrFeO2.5 phase is not stable even in inert atmosphere conditions, and a favorable trend is observed for orderly oxygen deficiency in atmospheres with higher oxygen content. In addition, to define a maximum structural integrity temperature for the SrFeO2.5 phase of 750 ° C. The phases resulting from the oxygen deficiency induced in the TGA were characterized by driving XRD and SEM-FE.

La deficiencia de oxígeno en el sistema SrFeO2.5 resulta de interés científico debido al comportamiento estructural de este material al ser expuesto en ambientes de trabajo termodinámicamente controlados y no controlados. Además, al ser empleado como fase precursora de materiales cerámicos más complejos es sometido a una atmósfera altamente reductora. Sin embargo, al ser puesto en contacto en condiciones ambientales presenta una descomposición paulatina, producto del potencial químico de la fase aniónica que promueve la deficiencia ordenada de oxígeno derivando en una mezcla SrFeO2.5+SrFeO2 con un alto porcentaje de la fase SrFeO2 teóricamente inestable. En este trabajo polvos precursores de SrCO3 (Aldrich, 99.9%) y Fe2O3 (Alfa Aesar, 99.9%) fueron deshumidificados en un horno de lecho seco durante 20 h a 100°C. Después, fueron mezclados en relación 2:1 en un mortero de ágata durante 1h para su posterior carga en una balanza termogravimétrica donde se llevó a cabo la síntesis de la fase SrFeO2.5. Una vez obtenida la fase fue caracterizada por DRX y se comprobó una ruta exitosa y reproducible para la síntesis de la fase SrFeO2.5. Para el análisis de la deficiencia ordenada de oxígeno muestras de la fase SrFeO2.5 fueron sometidas a atmósferas inertes, reductoras y oxidantes dentro de una termobalanza, y al ambiente expuestas a la intemperie. Empleando los resultados del análisis termogravimétrico (TGA) se relacionó la pérdida de peso con la pérdida de oxígeno calculada mediante un balance de materia. Se demostró que la fase SrFeO2.5 no es estable incluso en condiciones de atmósfera inerte, y observándose una tendencia favorable para la deficiencia ordenada de oxígeno en atmósferas con mayor contenido de oxígeno. Además, de definir una temperatura máxima de integridad estructural para la fase SrFeO2.5 de 750°C. Las fases resultantes de la deficiencia de oxígeno inducida en el TGA fueron caracterizadas empelando DRX y SEM-FE.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Metalurgia y Ciencias de los Materiales
Keywords: info:eu-repo/classification/cti/7; IIMM-M-2017-0593; Termogravimetría; Cálculo de defectos; Temperatura crítica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5289